KAJIAN PENAMBAHAN NATRIUM PYROPHOSPAT UNTUK MENCEGAH BROWNING PADA PEMBUATAN TEPUNG SUKUN - Edahwati, Luluk; S, Kalimatus; Nuraini, Dian (UPN VETERAN JAWA TIMUR, 2010)
Like most fruit - fruit, breadfruit prone to browning after peels. This is due to oxidation by air, forming browning, which will result in the final result breadfruit flour for making good quality flour is white, and dry. Pyrophospat Sodium is an ingredient that can serve as a barrier to browning reactions, primarily as a metal fastener and thus antioxidants Pyrophospat Sodium is very effective to prevent discoloration of foods during preparation or storage. The best results obtained from this research is the weight of 9 grams Sodium Pyrophospat soaking 21 minutes in which the resulting yield of 21.69%. While the best water content of 8.09% with the use of one gram of sodium Pyrophospat with immersion time for 9 minutes.Keywords: Breadfruit, Sodium Pyrophospat, Breadfruit Flour.